Access to HIV prevention services in East African cross‐border areas: a 2016‐2017 cross‐sectional bio‐behavioural study. (30th June 2020) - Virkud, Arti V; Arimi, Peter; Ssengooba, Freddie; Mulholland, Grace E; Herce, Michael E; Markiewicz, Milissa; Weir, Sharon; Edwards, Jessie K
Abstract: Introduction: East African cross‐border areas are visited by mobile and vulnerable populations, such as men, female sex workers, men who have sex with men, truck drivers, fisher folks and young women. These groups may not benefit from traditional HIV prevention interventions available at the health facilities where they live, but may benefit from services offered at public venues identified as places where people meet new sexual partners (e.g. bars, nightclubs, transportation hubs and guest houses). The goal of this analysis was to estimate availability, access and uptake of prevention services by populations who visit these venues. Methods: We collected cross‐sectional data using the Priorities for Local AIDS Control Efforts sampling method at cross‐border locations near or along the land and lake borders of Kenya, Rwanda, Tanzania and Uganda from June 2016–February 2017. This bio‐behavioural survey captured information from a probability sample of 11, 428 individuals at 833 venues across all areas. Data were weighted using survey sampling weights and analysed using methods to account for the complex sampling design. Results: Among the 85.6% of persons who had access to condoms, 60.5% did not use a condom at their last anal or vaginal sexual encounter. Venues visited by high percentages of persons living with HIV were not more likely than other venues to offer condoms. In 12 of the 22 cross‐border areas, male or female condoms were available at less than 33% of the venues visited by persons having difficulty accessing condoms. In 17 of the 22 cross‐border areas, education outreach visits in the preceding six months occurred at less than 50% of the venues where participants had low effective use of condoms. Conclusions: Individuals visiting venues in cross‐border areas report poor access to and low effective use of condoms and other prevention services. Availability of HIV prevention services differed by venue and population type and cross‐border area, suggesting opportunities for more granular targeting of HIV prevention interventions and transnational coordination of HIV programming.